Evaluation of Surface Roughness of Different Esthetic Restorative Materials after Immersion in Different Acidic Media - Elmarakby, Ahmed M.; Alanazi, Atheer M.; Alotaibi, Nujood; Al Bahrain, Isra; Alshamali, Renad; Ameer, Sarah Mohammed; Lsloom, Shahad; Khaled, Haneen (Open Access Macedonian Journal of Medical Sciences, 2022)
Abstract: Background: Dental erosion that resulted from increasing the acidity of oral conditions not only affects tooth substrates but also the performance of some esthetic restorations. Objective: The aim of the current study was to measure and evaluate the surface roughness of different tooth colored restorative materials (resin composites) after immersion for certain time in different acidic food and drinks. Material and method: Three types of composite restoration have been used in this study. The three types were of three main groups. Each group of twenty specimens (n= 20) were divided according to type of acidic media they were immersed in into five sub-groups (n=4). Different acidic beverages and drinks were used in this study include Coke Cola soft drink, orange juice, Pepsi soft drink, sports drink, and lemon juice. Immersion of specimens’ in previously mentioned acidic drinks were for 5 minutes then they have been immersed in distilled water to simulate to great extent what happened in oral cavity. These procedures repeated daily for 14 days. Surface roughness for specimens have been measured by a profilo-meter (Talysurf CLI 1000, Leicester, England) device before and after immersion. Data were collected, tabulated and analyzed using one-way ANOVA. Results: The assessment of surface roughness by one-way ANOVA and Tukey’s post hoc tests showed significant differences for composite material types as well as an interaction between these parameters for each composite after immersion in different acidic beverages (P<.05). Conclusion: Within the limitation of this study, results revealed that composition of both resin composite and different acidic beverages and drinks play an important role in initiation and conduction of surface roughness at the outer surface of resin composite restoration.